Scientism : the new orthodoxy - Robinson, Daniel N., 1937-; Williams, Richard N., 1950- (Bloomsbury Academic, 2014)
"Scientism: The New Orthodoxy is a comprehensive philosophical overview of the question of scientism, discussing the place of science in the humanities and religion. Clarifying and defining the key terms in play in discussions of scientism, this collection identifies the dimensions that differentiate science from scientism. Leading scholars appraise the means available to science, covering the impact of the neurosciences and the new challenges it presents for the law and the self. Illustrating the effect of scientism on the humanities, Scientism: The New Orthodoxy addresses what science is. This provocative collection is an important contribution to the humanities in the 21st century. Contributors include: Peter Hacker, Bastian van Fraassen, Kenneth Schaffner, Roger Scruton, James K.A. Smith, Richard Swinburne, Lawrence Principe and Richard Williams"--